2014
DOI: 10.4049/jimmunol.1400255
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Neutrophil Extravasation by α2-Adrenoceptor–Mediated Endothelial Stabilization

Abstract: Adrenergic receptors are expressed on the surface of inflammation-mediating cells, but their potential role in the regulation of the inflammatory response is still poorly understood. The objectives of this work were to study the effects of α2-adrenergic agonists on the inflammatory response in vivo and to determine their mechanism of action. In two mouse models of inflammation, zymosan air pouch and thioglycolate-induced peritonitis models, the i.m. treatment with xylazine or UK14304, two α2-adrenergic agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…In addition, in an animal model of TPA‐induced acute inflammation and in an in vitro assay of acute vascular inflammation, brimonidine significantly reduced neutrophil recruitment. Furthermore, a decrease in neutrophil content in inflammatory foci in vivo with a systemic treatment with α2‐adrenergic agonists was previously observed, which is in line with the present results …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, in an animal model of TPA‐induced acute inflammation and in an in vitro assay of acute vascular inflammation, brimonidine significantly reduced neutrophil recruitment. Furthermore, a decrease in neutrophil content in inflammatory foci in vivo with a systemic treatment with α2‐adrenergic agonists was previously observed, which is in line with the present results …”
Section: Discussionsupporting
confidence: 93%
“…In addition, α2A‐adrenergic receptors are also expressed in endothelial cells and human neutrophils. Moreover, α2‐agonists trigger signals that protect the integrity of endothelial adherent junctions during the inflammatory response . Moreover, we showed that endothelial cells are the main targets of α2A‐adrenergic agonists.…”
Section: Discussionmentioning
confidence: 78%
“…Brimonidine acts by selectively binding to α2‐adrenergic receptors present on smooth muscle in the peripheral vasculature, resulting in transient local vasoconstriction and other vascular effects (Table ). Other α2 receptor agonists have further demonstrated the ability to reduce neutrophil extravasation and inhibit PGE2 release …”
Section: Targeted Mechanisms Of Current Rosacea Therapeuticsmentioning
confidence: 99%
“…In the context of peripheral inflammation, while COX‐2 inhibition was shown to attenuate neutrophil‐endothelium interaction, a key step in inflammation‐evoked endothelial dysfunction in PE, a similar role for α 2 ‐AR modulation in this process cannot be discounted. Indeed, an anti‐inflammatory role for α 2 ‐AR agonists, evident by decreased endothelial‐leukocyte interaction, has been reported . α 2 ‐AR agonists caused an increase in the resistance of ECs to neutrophil extravasation, through inhibition of TNF‐α‐decreased expression of adhesion molecules .…”
Section: Inflammation Potentially Links α2‐ar Function To Pathogenesimentioning
confidence: 99%
“…Indeed, an anti‐inflammatory role for α 2 ‐AR agonists, evident by decreased endothelial‐leukocyte interaction, has been reported . α 2 ‐AR agonists caused an increase in the resistance of ECs to neutrophil extravasation, through inhibition of TNF‐α‐decreased expression of adhesion molecules . Of course, more studies are needed to investigate the anti‐inflammatory effect of α 2 ‐ARs in placental preeclamptic tissues and animal models.…”
Section: Inflammation Potentially Links α2‐ar Function To Pathogenesimentioning
confidence: 99%